Legal Review of Corporate Liability Based on Law Number 1 of 2023 concerning the Criminal Code - Arfia Arfia; Irabiah Irabiah; La Ode Awal Sakti; Basrawi Basrawi; Muh. As Ari AM (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2025)
Corporations play a significant role in the economic development of society, but they not only have positive impacts, but also cause negative, deviant impacts. where the characteristics and movements are different from conventional crimes in general. Unclear regulations on corporate criminal liability are a major obstacle in eradicating criminal acts committed by corporations. Although corporations have been designated as legal subjects. This research focuses on the study of the regulation of corporate criminal liability based on Law Number 1 of 2023 and to determine the concept of criminalization of corporations as perpetrators of criminal acts. This research uses a normative research method, which focuses on collection and analysis with a statutory approach, a case approach, and a conceptual approach. The results of the study concluded that in Law Number 1 of 2023 concerning the Criminal Code, in addition to two forms of error (intentional and negligence), it also regulates unlawful acts that can be held criminally accountable to corporations and shareholders where each article formulation requires that every act and the consequences of the act must be intended by the perpetrator to be held criminally accountable. The imposition of corporate criminal liability is regulated in Articles 45-50 of Law Number 1 of 2023 concerning the Criminal Code, strengthening the teaching/doctrine of piercing the corporate veil in imposing criminal liability on shareholders who commit crimes.